Evolution, trends and design parameters for the management of Areas of Logistic Activities in Spain - Romero Postiguillo, José; Yagüe, José María Del Campo; Santamera Sánchez, Juan Antonio (Revista de la Construcción. Journal of Construction, 2017)
In the last 50 years a new organization of international markets that directly affects procurement systems, production, and distribution has been developed, the supply chain. In this new globalized trade setup logistics is particularly relevant and unique, occupying preferential status in the competitiveness of products and companies. The transport system necessary for the supply and distribution is linked to linear and nodal infrastructures, both essential for the logistic chain. Within the nodal infrastructure, we find Logistics Platforms, which not only act as support to the infrastructure itself, but also provide value-added services and are configured as the main points of the supply chain, providing companies with the ability to implement some of the above mentioned logistic activities, in order to match demand and supply, thus optimizing the supply chain and reducing logistics’ costs. Since there is no regulation and standardization to support the design of these “Logistics Areas”, we will proceed to analyze 33 emblematic Spanish Logistics Platforms. This study will focus on the analysis of the role or relevance of logistics centrality, its intermodality, the degree of spatial concentration, the multifunctional level or the sector-specific expertise, and internal management. As a final point, the paper offers recommendations and standards for its design and management as well as a new definition of Logistics Activity Area.